2020
DOI: 10.1038/s41467-020-14955-0
|View full text |Cite
|
Sign up to set email alerts
|

Vertical eddy iron fluxes support primary production in the open Southern Ocean

Abstract: The primary productivity of the Southern Ocean ecosystem is limited by iron availability. Away from benthic and aeolian sources, iron reaches phytoplankton primarily when iron-rich subsurface waters enter the euphotic zone. Here, eddy-resolving physical/biogeochemical simulations of a seasonally-forced, open-Southern-Ocean ecosystem reveal that mesoscale and submesoscale isopycnal stirring effects a cross-mixed-layer-base transport of iron that sustains primary productivity. The eddy-driven iron supply and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 50 publications
6
42
0
Order By: Relevance
“…If nutrients are transported upward primarily by ocean plumes, we would expect detrainment to release these nutrients in the ocean interior. In Earth's ocean, it has been shown that adiabatic mixing, or stirring along isopycnals, can be an important pathway for nutrient delivery to the surface and modulate productivity there [26].…”
Section: Discussionmentioning
confidence: 99%
“…If nutrients are transported upward primarily by ocean plumes, we would expect detrainment to release these nutrients in the ocean interior. In Earth's ocean, it has been shown that adiabatic mixing, or stirring along isopycnals, can be an important pathway for nutrient delivery to the surface and modulate productivity there [26].…”
Section: Discussionmentioning
confidence: 99%
“…They form preferentially in the upper and bottom turbulent boundary layers (Lévy et al, 2012) and are characterized by O(1) Richardson and Rossby numbers, with horizontal scales between 100 m and a few kilometers, and characteristic time scales from hours to days . The vertical velocity field induced by submesoscale circulations is ephemeral but can exceed 10 −3 m s −1 and may extend to several hundred meters of depth, bringing nutrient-rich waters into or out of the euphotic layer, and exporting organic carbon out of the surface layer (e.g., Omand et al, 2015;Uchida et al, 2020). The rapid physical exchange between surface and deep waters may affect the structure and functions of the local marine ecosystem by stimulating near-surface or sub-surface phytoplankton blooms or by changing the properties of water masses (Mahadevan and Archer, 2000;Lévy et al, 2001;Pidcock et al, 2010;Clayton et al, 2014;Lévy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Winds and waves strongly modulate ocean mixing (Thorpe, 2007;Toffoli et al, 2012), biological production (Nicholson et al, 2016;Uchida et al, 2020), air-sea gas exchange (Wanninkhof et al, 2009;Gruber et al, 2019), sea ice dynamics Vichi et al, 2019) and sea spray emission (Figure 1f), relevant for cloud formation (Schmale et al, 2019;Quinn et al, 2017;Bigg, 1973). This storm track region is characterised by the frequent passage of extratropical cyclones leading to the formation of a quasi-persistent low-level cloud deck and regular precipitation (Figure 1g) (Catto et al, 2012).…”
Section: Introductionmentioning
confidence: 99%